Heuristic algorithms for dynamic scheduling of moldable tasks in multicore embedded systems - Takuma Hikida; Hiroki Nishikawa; Hiroyuki Tomiyama (Institute of Advanced Engineering and Science, 2021)
Dynamic scheduling of parallel tasks is one of the efficient techniques to achieve high performance in multicore systems. Most existing algorithms for dynamic task scheduling assume that a task runs on one of the multiple cores or a fixed number of cores. Existing researches on dynamic task scheduling methods have evaluated their methods in different experimental environments and models. In this paper, the dynamic task scheduling methods are systematically rearranged and evaluated.